2019
DOI: 10.1108/jiabr-04-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

DoesShariahcommittee composition influenceShariahgovernance disclosure?

Abstract: Purpose The purpose of this paper is to investigate the empirical linkage between the composition of Shariah Committee and the extent of Shariah governance disclosure in 16 licensed Islamic banks in Malaysia. Design/methodology/approach This paper adopted a multiple regression analysis to test the association between the composition of Shariah Committee and the extent of Shariah governance disclosure. A disclosure index was developed to measure the extent of Shariah governance disclosure made by the Islamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 58 publications
5
50
1
2
Order By: Relevance
“…Size of the shariah Supervisory Board has a probability value of 0.0153 greater than the significance of 0.05 (0.0153 <0.05, so H0 Rejected which means size of the shariah Supervisory Board has a positive effect on the disclosure of shari'ah. It means that the large number of DPS members will have an impact on the desire to disclose sharia compliance in sharia bank financial statements [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Size of the shariah Supervisory Board has a probability value of 0.0153 greater than the significance of 0.05 (0.0153 <0.05, so H0 Rejected which means size of the shariah Supervisory Board has a positive effect on the disclosure of shari'ah. It means that the large number of DPS members will have an impact on the desire to disclose sharia compliance in sharia bank financial statements [13].…”
Section: Resultsmentioning
confidence: 99%
“…It has a partial meaning that the Cross Membership of the sharia supervisory board variable has no effect on the disclosure of shari'ah. It means that this means that the number of DPS memberships in professional organizations does not impact on the desire to disclose sharia compliance [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IA and CF are also included as sharia governance organs involved in the sharia supervision process. The majority of studies testing the SSB's performance were conducted by Haridan et al, (2018), Violita & Handarbeni (2017), Noordin & Kassim (2016), Rahman & Bukair (2013). Thus, further research into the role of IA and CF in sharia compliance is needed.…”
Section: Consideringmentioning
confidence: 99%
“…Haji and Ghazali (2013), on Noordin & Kassim (2016), indicated that a greater number of members in a governance body should provide more collective knowledge and skills. Moreover, the diversity of knowledge and skills and experience among such members is believed to facilitate the supervision process of sharia compliance (Rahman & Bukair, 2013).…”
Section: Number Of Internal Audit and Compliance Function Membersmentioning
confidence: 99%